Films based on the biopolymer poly(3-hydroxybutyrate) as platforms for the controlled release of dexamethasone - Villegas, Mercedes (2019)
Controlled drug delivery aims to achieve an effective drug concentration in the action site for a desired period of time, while minimizing side effects. In this contribution, biodegradable poly(3-hydroxybutyrate) films were evaluated as a reservoir platform for dexamethasone controlled release. These systems were morphological and physicochemically characterized. In vitro release assays were performed for five different percentages of drug in the films and data were fitted by a mathematical model developed and validated by our research group. When the profiles were normalized, a single curve properly fitted all the experimental data. Using this unique curve, the dissolution efficiency (DE), the time to release a given amount of drug (tX%), and the mean dissolution time were calculated. Furthermore, the dissolution rate, the initial dissolution rate (a%) and the intrinsic dissolution rate were determined. The a% mean value was 1.968 × 10−2% released/min, t80% was about 14 days, and the DE was 59.6% at 14 days and 66.5% at 20 days. After 2 days, when approximately 40% of the drug was released, the dissolution rate decreased about 60% respect to the initial value. The poly(3-hydroxybutyrate) platforms behaved as an appropriate system to release and control the dexamethasone delivery, suggesting that they could be an alternative to improve drug therapy.